Gerakan Politik Sarekat Islam di Jawa Tahun 1916-1921 - Yeti Setiawati; Samsudin Samsudin (Historia Madania: Jurnal Ilmu Sejarah, 2020)
Sarekat Islam is a movement organization that has a very important role in fighting for independence of Indonesia. In the beginning, this organization was established to overcome only economic problems in the lives of indigenous people. As it develops, this organization also turned into a political organization that aims to realize self-government. This research is an analysis of political movements conducted by Sarekat Islam which began from 1916 to 1921. The research uses a historical study method of heuristic, critic, interpretation, and historiography. This study uses a theory of structure of political opportunity with a science approach that is political sociology approach. The result of this study indicates that the Sarekat Islam political movement was realized with a national congerss held to discuss various political problems including the formation of a Volksraad, the defense of the Dutch East Indies (Indie Weerbaar) and others. Until in the end, Sarekat Islam divided into Sarekat Islam Merah dan Sarekat Islam Putih.